Capital-based regulation, portfolio risk and capital determination: Empirical evidence from the US property–liability insurers - Shim, Jeungbo (Journal of Banking & Finance, 2010)
This paper examines the impact of capital-based regulation on the insurer’s risk and capital adjustments in the US property–liability insurance industry. We conduct the three-stage least squares (3SLS) procedure to estimate a simultaneous equations model. The key finding is that undercapitalized insurers increase capital to avoid regulatory costs and take more risks to generate higher returns. We also investigate firm characteristics that determine the insurer’s capital structure. The results indicate that insurers appear to rely heavily on retained earnings to make up their capital shortage and insurers with greater growth opportunity may hold high levels of capital to control for agency problems. Robustness tests with an alternative risk measure and subsamples present consistent results.